The Legal Due To The Pre-Married Agreement Concerning Collective Property Made With Authentic Assets - Lestari Diah Ayuningtyas (Sultan Agung Notary Law Review, 2020)
The research objective is to find out and explain the agreement on pre-marital joint property in front of a notary in the Purwokerto jurisdiction, and to find out and explain the legal consequences of a pre-marital joint property agreement in front of a notary in the Purwokerto jurisdiction.juridical sociological approach method. The specification used in this research is descriptive research.Based on the qualitative analysis, it is known thatThe legal consequences of pre-marital joint property agreements in front of a notary public and legalized by a marriage / marriage registrar are binding and valid as law for the prospective husband and wife and third parties, as far as the party is concerned. If the Marriage Agreement that has been made by the husband and wife is not implemented or there is a violation of the agreement made, it automatically gives the wife the right to request an annulment of the marriage or as a reason for a divorce suit.Keywords :    Because of law, Pre-Marriage Agreement, Joint Assets, authentic deed